Analisis Analisis Nilai 8 Dimensi Profil Lulusan dalam Puisi-puisi Remaja Karya Amalia Najichah pada Antologi Puisi Berjudul Surat Dari Samudera - Vani Indra Pramudianto; Eko Suroso (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to analyze the representation of character values within the Eight Dimensions of Graduate Profiles aligned with the vision of the Pancasila Student Profile in Amalia Najichah’s poems from the anthology Surat dari Samudera (Letters from the Ocean). The research employs a qualitative approach using content analysis, complemented by stylistic and literary reception theories. The data consist of six poems analyzed based on eight character dimensions: Faith and Piety to God Almighty, Citizenship, Critical Thinking, Creativity, Collaboration, Independence, Health, and Communication. The findings reveal that all poems reflect these character values, with Citizenship and Collaboration as the most dominant dimensions. Stylistic analysis shows that the use of repetition, metaphor, and onomatopoeia not only enhances aesthetic quality but also reinforces moral and social messages. Meanwhile, reception theory analysis indicates that young readers can internalize these values cognitively, affectively, and socially through reflective and contextual reading experiences. The study concludes that youth poetry has strong potential as an effective medium for character education in the Merdeka Curriculum, both in intracurricular and co-curricular contexts. Therefore, Amalia Najichah’s works serve not only as aesthetic expressions of adolescence but also as strategic instruments for shaping a faithful, independent, collaborative, and Pancasila-oriented generation.